EFEKTIVITAS KEBIJAKAN ALOKASI DANA DESA DI DESA NANGA KEBEBU KECAMATAN NANGA PINOH KABUPATEN MELAWI - Nur E.01110056, Anggi Wanti Safitri (FISIP Universitas Tanjungpura, 2014)
The purpose of this study is to describe and analyze the outcome of fund allocation policy in the village of Nanga Kebebu, Nanga Pinoh subdistrict of Melawi Regency. The study used is qualitative approach with descriptive research. The result of the study is that the impact achieved through the development of ADD was still less effective; from 9 programs that had been designed, only 1 program had been implemented through ADD. This affected the outcome or impact generated that was not maximal and not evenly occurred on entire villages. Second, from ADD budget that reached Rp. 26,559,793, only Rp 3,000,000 was allocated for rural development that had been planned. Third, the development program that had been implemented: building village’s gate, was not in accordance with what was desired and needed by society; people prefer empowerment based development. Fourt, there was uneven development impact which was focused on the center of the village. Recommendations for future policy are that procedures and technical for the implementation of village’s fund allocation policy should be clarified. Key words: Village Fund Allocation, development of village, outcome of ADD’s policy, effectiveness.